Biohydrogen production via thermophilic fermentation: A prospective application of Thermotoga species. (15th April 2020) - Shao, Weilan; Wang, Qiang; Rupani, Parveen Fatemeh; Krishnan, Santhana; Ahmad, Fiaz; Rezania, Shahabaldin; Rashid, Muhammad Adnan; Sha, Chong; Md Din, Mohd Fadhil
Abstract: Considering the era of industrialization and increasing growth of interest in the green bioconversion of biomass into efficient value-added products, this review discusses the hydrogen (H2 ) production using the hyperthermophilic bacteria as a promising strategy for the agriculture and industrial purposes towards the generation of clean energy. Production of microbial enzymes through hyperthermophiles is beneficial as they are more resistant and stable in a controlled closed production system. Among hyperthermophile bacteria, thermotogales include species with the ability to grow optimally at temperatures ≥80 °C and to produce high yields of H2 . Thermostable enzymes are able to degrade different biomass materials and produce H2, it attained much attention for the scholars and have been used at the industrial scale. The biohydrogen pathways of thermotogales and the obstacles during the fermentation process need to be deeply examined. Therefore, this work critically reviewed the hydrogen production of Thermotoga species and their application to different biomass. Moreover, a critical discussion on the hyperthermophilic hydrogenic bacteria is provided followed by its genetic modifications and challenges associated to realize its future sustainability. In addition, this paper discusses the challenges of improving hydrogen production. Finally, it was concluded that using thermostable enzymes produced by extremophilic bacteria such as T. maritima will lead to green development through producing high hydrogen yields. Highlights: Thermotogales species with the ability to grow at temperatures ≥ 80 °C, and able to produce high amount of hydrogen. Thermothogales owes thermostable enzyme to degrade different biomass material. The mechanism of hydrogen production from biomass of Thermotoga species is critically reviewed and clarified. Genetic modifications and challenges associated to realize its future sustainability have been discussed.